Psychology and Necropolitics: A Critical Analysis of 'High-Impact' Publications on Violence in Ecuador - Capella, Manuel; Rodas , José Antonio (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2024)
This article reviews psychological research on violence in Ecuador, focusing on high-impact publications indexed in Scopus. Although analyzed studies cover various forms of violence, such as gender-based violence and violence against minors, they tend to focus on individual and interpersonal levels, with a predominance of hegemonic theories imported from the United States and Europe. This approach limits the understanding of the complex sociopolitical dynamics that determine the conditions of life and death in the country. Among others, one example of this limitation is the absence of the concept of necropolitics, which is essential to examine how power structures determine who is considered expendable in contexts of extreme violence, such as the COVID-19 health crisis and drug-related violence in Ecuador. Incorporating necropolitical analysis into psychological research would allow for a deeper understanding of how these forces operate, underscoring the need for inter- and transdisciplinary approaches that transcend individualistic perspectives and better represent the social and political realities of Ecuador.